Emotional resilience and sense of danger among doctors in hospitals during periods of heightened tensions and warfare in Israel - Michael V. Joachim; Dana Atia Joachim; Liat Korn; Yair Shapiro; Amir Laviv; Avi Zigdon (Israel Journal of Health Policy Research)
Abstract Background The “Iron Swords” War beginning in October 2023 led to unprecedented levels of shock and trauma across Israel, significantly impacting the Israeli population and medical personnel. This study aimed to evaluate and compare the perceived personal resilience and sense of danger among physicians in hospitals located in different conflict zone proximities in Israel during this period. Methods A quantitative, cross-sectional study was conducted from March to August 2024, during an active phase of the war, using a structured anonymous questionnaire. Participants were 161 physicians from three hospitals: one in southern Israel near the Gaza Strip, another in northern Israel near the borders with Lebanon, Syria, and Jordan, and a third in central Israel near Tel Aviv. The survey measured personal resilience using the Connor-Davidson Resilience Scale (CD-RISC-10) and sense of danger using the Solomon & Prager scale. Statistical analyses included Kruskal-Wallis H test, multiple linear regression, two-way analysis of variance (ANOVA), and Sobel test for mediation effects. Results The final sample included 161 physicians (54 southern, 56 central, 51 northern). The mean resilience score was 31.14 ± 5.77, and the mean sense of danger score was 8.36 ± 4.15 (scales 0–40 and 0–20, respectively). Physicians in the southern hospital reported significantly higher sense of danger scores (p = 0.005). A trend towards lower resilience scores was noted among southern hospital physicians (p = 0.068) (p = 0.068). Two-way ANOVA revealed significant main effects of hospital location and gender on resilience (p = 0.046 and p = 0.003, respectively) and sense of danger (p = 0.005 and p = 0.062, respectively). Multiple regression analysis identified hospital location (β = -0.178, p = 0.023) and gender (β = 0.229, p = 0.004) as significant predictors of resilience. Mediation analysis indicated that personal resilience partially mediated the relationship between hospital location and sense of danger (indirect effect = 0.2896, p < 0.001). Conclusions Physicians working near conflict zones report higher levels of perceived danger, though their resilience is comparable to peers in less threatened regions. Enhancing personal resilience is crucial to mitigate the heightened sense of danger. This could include regular resilience training, psychological support, and specific programs for single and childless physicians to improve safety perceptions. Additionally, fostering a supportive community with clear communication and robust emergency protocols is essential for enhancing staff resilience and safety in hospitals.